2002
DOI: 10.1152/ajplung.00406.2000
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cell proliferation and programmed cell death by dexamethasone during postnatal lung development

Abstract: Prematurely born babies are often treated with glucocorticoids. We studied the consequences of an early postnatal and short dexamethasone treatment (0.1–0.01 μg/g, days 1–4) on lung development in rats, focusing on its influence on peaks of cell proliferation around day 4 and of programmed cell death at days 19–21. By morphological criteria, we observed a dexamethasone-induced premature maturation of the septa ( day 4), followed by a transient septal immatureness and delayed alveolarization leading to complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 24 publications
4
42
1
Order By: Relevance
“…Lungs were obtained from 129/SV mice according to Schittny and coworkers (1997;Luyet et al, 2002) between postnatal days 2 and 125. Briefly, after the lung collapsed in the closed thorax due to a punctuation of the diaphragm, the airspace was filled by tracheal installation with freshly prepared solution of 4% paraformaldehyde in phosphate buffered saline (10 mM sodium phosphate, containing 127 mM sodium chloride, pH 7.4) at a constant pressure of 20 cm water column.…”
Section: Animals and Tissuesmentioning
confidence: 99%
“…Lungs were obtained from 129/SV mice according to Schittny and coworkers (1997;Luyet et al, 2002) between postnatal days 2 and 125. Briefly, after the lung collapsed in the closed thorax due to a punctuation of the diaphragm, the airspace was filled by tracheal installation with freshly prepared solution of 4% paraformaldehyde in phosphate buffered saline (10 mM sodium phosphate, containing 127 mM sodium chloride, pH 7.4) at a constant pressure of 20 cm water column.…”
Section: Animals and Tissuesmentioning
confidence: 99%
“…During organ development, cells must pass through the various cell cycle stages in order to allow for continued remodelling. This process is essential to proper lung development (Bruce et al, 1999;Luyet et al, 2000). Consequently, the redox potential must also cycle continuously ( Figure 3).…”
Section: Redox Potential Of Glutathionementioning
confidence: 99%
“…A more oxidized state will also induce cell death by apoptosis. (Adapted from Schafer FQ et al, 2001) The link between redox potential and BPD can be explained by an exacerbated apoptosis rate caused by an abnormally elevated redox potential (Luyet et al, 2000). Lung samples from premature baboons with BPD (Das et al, 2004) showed a large number of apoptotic events.…”
Section: Redox Potential Of Glutathionementioning
confidence: 99%
See 1 more Smart Citation
“…Rat lung samples, prepared according to Tschanz and Burri [123] and Luyet et al [124] were used as test objects. Briefly, lungs of SpragueDawley rats were filled with 2.5 % glutaraldehyde (CH 2 (CH 2 CHO) 2 ) in 0.03 m potassium-phosphate buffer (pH 7.4) by instillation via tracheotomy at a constant pressure of 20 cm water column.…”
Section: Sample Preparationmentioning
confidence: 99%